2020
DOI: 10.1155/2020/4282398
|View full text |Cite
|
Sign up to set email alerts
|

Computation of Deflections for PC Box Girder Bridges with Corrugated Steel Webs considering the Effects of Shear Lag and Shear Deformation

Abstract: Prestressed concrete (PC) girders with corrugated steel webs (CSWs) have received considerable attention in the past two decades due to their light self-weight and high prestressing efficiency. Most previous studies were focused on the static behavior of CSWs and simple beams with CSWs. The calculation of deflection is an important part in the static analysis of structures. However, very few studies have been conducted to investigate the deflection of full PC girders or bridges with CSWs and no simple formulas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…Thus, the distribution of longitudinal strains along the width direction of the top plate of Beams A1 and A2 is uneven, indicating the presence of the shear lag effect, which is consistent with the findings of Ma et al [26], Chen at al. [27], and Ji et al [28]. Compared with Figure 23a,c, as well as Figure 23b,d, it can also be observed that the load is within the range of 220 kN, and the distribution of longitudinal strains along the width direction of the top plate of corroded CBCSWs is more uneven, that is, the shear lag effect of the top plate of corroded CBCSWs is more obvious.…”
Section: Strain Variations During the Loading Failure Processmentioning
confidence: 49%
See 1 more Smart Citation
“…Thus, the distribution of longitudinal strains along the width direction of the top plate of Beams A1 and A2 is uneven, indicating the presence of the shear lag effect, which is consistent with the findings of Ma et al [26], Chen at al. [27], and Ji et al [28]. Compared with Figure 23a,c, as well as Figure 23b,d, it can also be observed that the load is within the range of 220 kN, and the distribution of longitudinal strains along the width direction of the top plate of corroded CBCSWs is more uneven, that is, the shear lag effect of the top plate of corroded CBCSWs is more obvious.…”
Section: Strain Variations During the Loading Failure Processmentioning
confidence: 49%
“…Li et al [14] analyzed the shear ratio of a single-box, four-cell composite box girder with corrugated steel webs through a numerical simulation procedure. In addition, some researchers have also studied the other behaviors of beams with corrugated webs, including the torsional performance [15][16][17][18][19][20], fatigue performance [1,[21][22][23], cyclic behavior [24], shear lag effect [25][26][27][28], dynamic characteristics [29][30][31], creep behavior [32], long-term behavior [3,33], natural frequency [34], distortion effect [35], and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Through theoretical derivation, finite element analysis, and model experiments, Liu Baodong et al [36] demonstrated the necessity of accounting for shear lag and shear deformation effects in deflection calculations for waveform steel web composite box girders. Ji Wei et al [37] derived a shape function to address the warping caused by shear lag in waveform steel web box girders and proposed a deflection calculation method considering both shear lag and shear deformation. Cheng et al [38] proposed deflection calculation formulas for single-cell and multi-cell waveform steel web composite box girders, assessing the impacts of shear lag and shear deformation on deflection.…”
Section: Introductionmentioning
confidence: 99%
“…e influence of various factors on the deflections of the box girders with CSW was analyzed. Based on the experimental model of CSWS composite box girder bridge, Wei et al [13,14] derived the longitudinal displacement functions and the deflection calculation equations of the composite box girders with CSW and determined the main influential factors on deflections under different width span ratios and corrugated steel web heights. Zhou et al [15] analyzed the shear lag effect of nonprismatic composite box girder with corrugated steel webs in the elastic stage.…”
Section: Introductionmentioning
confidence: 99%